Scope of Allegation of Forgery Regarding Customary Legal Title and the Ways to Reduce It In light of the Palestinian Evidence Law: A Comparative Analytical Study - Algherbawi, Yousef Abdullah (Journal of Economic, Administrative and Legal Sciences, 2022)
This study is titled: "Scope of Allegation of Forgery Regarding Customary Legal Title and the Ways to Reduce It In light of the Palestinian Evidence Law" - A Comparative Analytical Study" which aims in the first place at clarifying the legal treatment of this allegation, and how efficent is this treatment in reducing the effects of this allegation on the legal power of the customary legal titles without prejudice to the defensive rights of parties and the positive role of judge while hearing the civil actions; as this may open the way for a party to resort such allegation mala fide or through abusing of the defensive rights, which may obstruct the letigation procedures before judiciary, reaching at the end of this study to the possible ways to limit the use of this allegation. The study ended with number of conclusions and recommendation, including but not limited to, adopting some standards in organizing the customary legal titles, reviewing the legal texts regualting the forgery allegation, activating the role of the judge in reducing the effects of such allegation, and stipulating the legal texts that limit and minimize its use by the parties mala fide (in bad faith), plus considering the principle of compensation for the arbitrariness in litigation, penal endowment, and mandatory and non-mandatory fines. The research will depend on an analytical approach In line of the texts contained in the Palestinian Evidence Law, and the opinions of legal scholars pertainant to this topic, with reference to judicial rulings, and comparing them with the position of some other legislations as the study may require.
Keywords: Title; Customary; Forgery; Allegation; Parties; Denial